PERFORMANCE EVALUATION OF SIGNALIZED INTERSECTION AT AREA D USING VISSIM MICROSIMULATION AND HCM 2010 - Kullaya, Damian; Gayatri Kusumawardhani , Rani; Katimba, Godfrey (Jurnal Teknik Sipil, 2026)
Traffic performance in a road network is significantly influenced by traffic flow at intersections. Area D, a signalized intersection located in Dodoma City,Tanzania experiences traffic congestion during peak hours, causing excessive vehicle delays when signals are in operation. The main objective of the study is to evaluate traffic performance of the existing intersection using Highway Capacity Manual (HCM 2010) and PTV VISSIM simulation during peak periods. Vehicle flow was measured during morning and evening peak periods, specifically at 06:00 to 10:00 AM and from 04:00 to 06:00 PM. The traffic composition during the morning peak consisted of light vehicles (46.95%), motorcycles (33.78%), and heavy vehicles (19.27%), while during the evening peak it consisted of light vehicles (46.46%), motorcycles (36.06%), and heavy vehicles (17.48%). Analysis using HCM 2010 indicated that the average delay was 55.16 pcu/sec during the morning peak and 115.14 pcu/sec during the evening peak. The average queue lengths were 131.2 m and 327.4 m, with Level of Service E and F during morning and evening peak hours, respectively. PTV VISSIM Version 11 results showed higher delays of 99.67 pcu/sec and 149.14 pcu/sec. Three improvement scenarios were evaluated using a micro-simulation approach. The third scenario, combining traffic signal optimization and geometric improvements, was identified as the most effective. This scenario reduced delays to 21.27 pcu/sec and 29.86 pcu/sec, decreased queue lengths to 29.86 m and 89.45 m, and improved level of service to B and C during morning and evening peak hours.